First limits on the very-high energy gamma-ray afterglow emission of a fast radio burst HESS observations of FRB 150418 - Colafrancesco, S.; Jingo, M.; Shafi, N.; Abdalla, H.; Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Andersson, T.; Angüner, E. O.; Arakawa, M.; Arrieta, M.; et al. (EDP Sciences, 2017)
Aims. Following the detection of the fast radio burst FRB150418 by the SUPERB project at the Parkes radio telescope, we aim to search for very-high energy gamma-ray afterglow emission. Methods. Follow-up observations in the very-high energy gamma-ray domain were obtained with the H.E.S.S. imaging atmospheric Cherenkov telescope system within 14.5 h of the radio burst. Results. The obtained 1.4 h of gamma-ray observations are presented and discussed. At the 99% C.L. we obtained an integral upper limit on the gamma-ray flux of Φγ(E > 350 GeV) < 1.33 × 10-8 m-2 s-1. Differential flux upper limits as function of the photon energy were derived and used to constrain the intrinsic high-energy afterglow emission of FRB 150418. Conclusions. No hints for high-energy afterglow emission of FRB 150418 were found. Taking absorption on the extragalactic background light into account and assuming a distance of z = 0.492 based on radio and optical counterpart studies and consistent with the FRB dispersion, we constrain the gamma-ray luminosity at 1 TeV to L < 5.1 × 1047 erg/s at 99% C.L.
Keywords: Gamma rays: general; Astroparticle physics; Tellurium compounds; Afterglow emission; Differential flux; Extragalactic background light; Gamma-ray observations; Imaging atmospheric Cherenkov telescopes; Very high energies; Gamma rays; COSMOLOGICAL DISTANCES; NEUTRON-STARS; ASTRONOMY; CATALOG; GALAXY